Assessing stress conditions and impact velocities in fluidized bed opposed jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Schott, Florian; Wirth, Karl Ernst; Peukert, Wolfgang (Particuology, 2020)
Fluidized bed opposed jet mills are capable of meeting the continuously growing demand for contamination-free fine particles. In this type of jet mill, the solid material is entrained and accelerated by expanding gas jets that are focused onto a focal point inside a fluidized bed. The resulting particle collisions induce breakage. The process is affected by the relative particle velocities and the number of particle–particle collisions. Clearly, both quantities are distributed. However, to date, neither relative particle velocities nor collision frequencies in such units have been determined. The present work introduces an innovative method to assess the stressing conditions in jet mills experimentally. To this end, mixtures of glass and ductile metal microspheres were used, with the latter employed in small amounts. Inter-particle collisions between the aluminum and glass spheres lead to the formation of dents on the microparticles. The size and number of these dents are associated with the individual collision velocities and overall collision frequencies. The correlation between dent size and collision velocity was obtained from finite element calculations based on empirical data. The proposed approach was validated using particle image velocimetry during secondary gas injection into a fluidized bed reactor. In this case the effect of the distance between two opposed nozzles was examined. For a lab-scaled fluidized bed opposed jet mill the effects of gas pressure and hold-up were investigated. Relative particle velocities were found to be significantly lower than the gas velocities, while the number of contacts per particle was determined to be extremely high.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Finite element modeling; Fluidized bed opposed jet mill; Relative velocity distribution; Single particle probes; Stress number distribution